2012
DOI: 10.1136/tobaccocontrol-2012-050591
|View full text |Cite
|
Sign up to set email alerts
|

Availability and range of tobacco products for sale in Massachusetts pharmacies

Abstract: Tobacco-free pharmacy policies would affect a majority of Massachusetts pharmacies and remove a variety of tobacco products from their store shelves. Further, nearly one in ten tobacco retailers would be eliminated by prohibiting tobacco sales in Massachusetts pharmacies statewide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…With regard to pharmacy bans, evidence from Massachusetts suggests that a pharmacy ban would remove nearly 10% of tobacco retailers in the state, based on the number of licensed pharmacies also holding a tobacco retailer license. 33 Our results indicate even greater reductions from a pharmacy ban in North Carolina, removing nearly 14% of retailers. The variation in estimated effects shown here given policy type, buffer zone distance and geographic locality offers support for estimating policy effects prior to policy selection.…”
Section: Discussionmentioning
confidence: 69%
“…With regard to pharmacy bans, evidence from Massachusetts suggests that a pharmacy ban would remove nearly 10% of tobacco retailers in the state, based on the number of licensed pharmacies also holding a tobacco retailer license. 33 Our results indicate even greater reductions from a pharmacy ban in North Carolina, removing nearly 14% of retailers. The variation in estimated effects shown here given policy type, buffer zone distance and geographic locality offers support for estimating policy effects prior to policy selection.…”
Section: Discussionmentioning
confidence: 69%
“…44,398,424,438,471,472,696,701,704,715,729,730,756774 The ENDS market is expanding 701,756 and accessible to consumers through internet vendors 472,729,769,771 and in most tobacco outlets. 472,704,729,730,758,759 Field observations of tobacco retail outlets have found that more than half of tobacco retailers sell ENDS. 438,729,730,762 One study found no significant relationship between retail availability and neighborhood demographics, 704 but another study indicated a greater likelihood of ENDS retailers in communities with higher median incomes.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Pharmacy/drug stores derive less than 2% of sales from tobacco products 7. However, nicotine replacement products are highly available in pharmacies,24 perhaps sparking availability of e-cigarettes as cessation devices or as products for more health-conscious smokers.…”
Section: Discussionmentioning
confidence: 99%